Invertebrate Trehalose-6-Phosphate Synthase Gene: Genetic Architecture, Biochemistry, Physiological Function, and Potential Applications - Tang, Bin; Wang, Su; Wang, Shi-Gui; Wang, Hui-Juan; Zhang, Jia-Yong; Cui, Shuai-Ying (Frontiers in Physiology, 2018)
The non-reducing disaccharide trehalose is widely distributed among various organisms. It plays a crucial role as an instant source of energy, being the major blood sugar in insects. In addition, it helps countering abiotic stresses. Trehalose synthesis in insects and other invertebrates is thought to occur via the trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) pathways. In many insects, the TPP gene has not been identified, whereas multiple TPS genes that encode proteins harboring TPS/OtsA and TPP/OtsB conserved domains have been found and cloned in the same species. The function of the TPS gene in insects and other invertebrates has not been reviewed in depth, and the available information is quite fragmented. The present review discusses the current understanding of the trehalose synthesis pathway, TPS genetic architecture, biochemistry, physiological function, and potential sensitivity to insecticides. We note the variability in the number of TPS genes in different invertebrate species, consider whether trehalose synthesis may rely only on the TPS gene, and discuss the results of in vitro TPS overexpression experiment. Tissue expression profile and developmental characteristics of the TPS gene indicate that it is important in energy production, growth and development, metamorphosis, stress recovery, chitin synthesis, insect flight, and other biological processes. We highlight the molecular and biochemical properties of insect TPS that make it a suitable target of potential pest control inhibitors. The application of trehalose synthesis inhibitors is a promising direction in insect pest control because vertebrates do not synthesize trehalose; therefore, TPS inhibitors would be relatively safe for humans and higher animals, making them ideal insecticidal agents without off-target effects.